(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2025)
This essay aims to test the categories and strategies of philosophy to reflect on one of the most common materials we encounter in our everyday experience: plastic. The first part moves from the historical conception of the plastic arts of two authors of the Goethezeit. Herder stresses the truthful dimension of the sense of touch and, consequently, of the plastic arts, while Hegel points out the transformative potential of plasticity. The second part focuses on Barthes’s essay Plastic, extrapolating three main theses: a) Plastic abolishes the hierarchy of substances; b) Plastic is not a substance, it is the very idea of transformation and has a negative constitution; c) Plastic is entirely swallowed up by use. In the third part, I will consider some contemporary artworks that precociously grasped the specificity and potential of plastics instantiating the conceptuality developed by Barthes and reactivating plasticity in plastic artworks.